Effects of Early Skip-A-Day Feed Removal and Litter Material on Broiler Live and Processing Performance and Litter Bacterial Levels - Lien, R.J.; Macklin, K.S.; Hess, J.B.; Dozier, W.A.; Bilgili, S.F. (International Journal of Poultry Science, 2008)
This study investigated effects of early skip-a-day feed removal and litter materials on broiler live and processing performance and levels of litter bacteria. A total of 1600 male broilers were evenly distributed in 16 pens. Eight pens were provided feed ad libitum (AL Treatment) and 8 were provided feed ad libitum except for 24 hour removal periods at 6, 8, 10 and 12 days of age (4R Treatment). Half the pens in each feeding treatment were provided used pine shavings and the other half were provided used sand as litter. An increasing photoperiod program was provided which decreased from 23L:1D to 13L:11D at 6 days, then increased 2 hours/week beginning at 13 days and reached 23L:1D at 41 days. Body weight and feed consumption were determined and feed conversions calculated approximately weekly. Mortalities were necropsied and recorded daily. At 47 days, 10 birds from each pen were processed, cut up and deboned to determine carcass and parts weights and yields. Litter samples were collected from 3 locations in each pen the day before chicks were placed, weekly during the rearing period and 9 days after bird removal. Relative to the AL Treatment, 4R body weights were decreased 27% immediately after feed removal, this smaller than expected reduction was likely due to the short photoperiod provided at that time. Body weights of AL and 4R Treatments diverged until partial compensatory growth occurred in the 4R Treatment once 23L:1D was provided. Feed consumption was reduced in the 4R Treatment following the initiation of feed removal, while feed conversion was only transiently reduced. Metabolic and total mortality were reduced by the 4R Treatment. Differences in carcass weights and yields and parts weights were proportional to live weight differences due to feeding treatments. Live production and processing performance were not influenced by litter material. In general, litter bacterial numbers were only influenced slightly by feeding treatments. However, litter type played a more marked role, with sand having lower aerobic, anaerobic and enteric counts than pine shavings.